Samaya Music Creation | Penciptaan Musik Samaya - I Putu Gede Yana Juliadinata; I Gede Yudarta (GHURNITA: Jurnal Seni Karawitan, 2024)
The Old Javanese Indonesian Samaya Dictionary comes from the Sanskrit language, namely a promise, which can be interpreted at a meeting that is agreed upon and agreed by two or more parties. The contract can be related to the trust of each partner, which can be expressed in sincere words such as mutual understanding, promise to live as long as death, promise always to be faithful, and promise to always take care of each other. The stylist was inspired to relate the above story to the wayang stories of Rama and Sita by using the media to reveal the gender of wayang. Gender wayang is a gamelan set and is generally used to accompany Balinese wayang kulit or wayang wong puppets. Creating this work is explained as making form and structure to the presentation arrangement of Samaya's work. The method of creation uses the method developed by Hawkins, namely the exploration stage, improvisation stage, and formation stage. The data collection techniques include library sources, audio and audio-visual recordings, and interviews. The stylist is interested in bringing up the story of love, loyalty, and the promise of a husband and wife. From this story, the stylist came up with an idea to make a source of inspiration into a new musical percussion art creation. All of these things interested the cultivators because the various atmospheres in achieving these goals, namely happiness, made them want to explore and pour them into creative percussion.